Ceramic matrix composite micro-hole drilling quality and material removal mechanism analysis method

By establishing a damage model and a finite element simulation model of ceramic matrix composite materials, the problems of easy breakage of drill bits and difficult to guarantee the quality of holes and entrances of holes during the drilling of ceramic matrix composite materials are solved, and the drill bit life and hole quality are improved.

CN119670469APending Publication Date: 2025-03-21AEROSPACE RES INST OF MATERIAL & PROCESSING TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411664398.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the drilling process of ceramic matrix composite micro-holes, the drill bit is prone to breakage and suffers severe losses, and the quality of the hole entrance and exit is difficult to guarantee.

Method used

The damage model of carbon fiber and SiC was defined by the 3D-Hashin failure criterion and JH2 model, and the damage model of the interface layer was defined by the law of linear elastic tensile tension, and a macroscopic and microscopic drilling finite element simulation model was established to perform simulation analysis to optimize the drilling parameters.

Benefits of technology

It effectively avoids breaking and loss of drill bits under inappropriate parameters, improves the quality of holes and outlets, improves the life of drill bits, and provides a parameter optimization basis for micro-hole holes of ceramic matrix composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119670469A_ABST
    Figure CN119670469A_ABST
Patent Text Reader

Abstract

A ceramic matrix composite micro-hole drilling quality and material removal mechanism analysis method comprises the following steps: determining a damage model and performance parameters of carbon fibers, a damage model and performance parameters of a SiC matrix, and a damage model and material attributes of an interface layer according to ceramic matrix composite micro-holes with the diameter phi of 0.5-2mm; a drill bit model and a ceramic matrix composite macroscopic model are established in simulation software, macroscopic finite element simulation is carried out, and a macroscopic finite element simulation result is obtained; a drill bit model and a ceramic matrix composite microscopic model are established in simulation software, microscopic finite element simulation is carried out, and a microscopic finite element simulation result is obtained. Carrying out a drilling test to obtain a test result; and comparing the test result, the macroscopic finite element simulation result and the microscopic finite element simulation result, and verifying the effectiveness of the macroscopic finite element simulation result and the microscopic finite element simulation result.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for analyzing the drilling quality and material removal mechanism of a ceramic-based composite micro-hole, in particular to a method for analyzing the drilling force, hole entrance and exit quality and material removal mechanism of a C / SiC composite micro-hole (diameter Φ0.5-2mm). Background Art

[0002] C / SiC composite material has both the high-temperature wear resistance and chemical stability of ceramics and the high strength and toughness of carbon fiber, and is a high-temperature structural material. Due to its light weight, high strength, high-temperature stability, wear resistance, corrosion resistance and other characteristics, it has been widely used in aviation, aerospace and other fields. The drill bit is severely worn during the processing of micro-holes in ceramic-based composite materials. The anisotropy of carbon fiber and the huge performance difference between carbon fiber and SiC make the workpiece surface susceptible to processing damage, such as pits, tears and burrs. In addition, due to the large ratio of the cutting edge length to the diameter of the micro-hole processing drill bit, the cutting edge is prone to bending and deformation during the processing. When the deformation is too large, the drill bit breaks. Therefore, drilling on composite materials is a major problem. In view of the above problems, the present invention proposes a method for analyzing the entrance and exit quality and material removal mechanism of micro-hole drilling in ceramic-based composite materials. The drilling process of ceramic-based composite materials is simulated and analyzed, which can effectively avoid the breakage and loss of the drill bit when drilling with inappropriate parameters; in addition, the analysis method is also of great significance for optimizing appropriate drilling parameters, improving the entrance and exit quality of holes, and increasing the life of the drill bit. Summary of the invention

[0003] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art and provide a method for analyzing the entrance and exit quality and material removal mechanism of drilling micro-holes (diameter Φ0.5~2mm) in ceramic-based composite materials, which can effectively avoid the breakage and loss of the drill bit when drilling with inappropriate parameters; in addition, the analysis method is also of great significance for optimizing suitable drilling parameters, improving the entrance and exit quality of the hole and increasing the life of the drill bit.

[0004] The purpose of the present invention is achieved through the following technical solutions:

[0005] A method for analyzing the entrance and exit quality and material removal mechanism of micro-hole drilling in ceramic matrix composite materials, comprising:

[0006] C / SiC composites are composed of carbon fibers and a filled SiC matrix, with two-dimensional carbon fibers as the reinforcement phase and SiC as the matrix phase.

[0007] (1) The 3D-Hashin failure criterion is used to define the damage model of carbon fiber.

[0008] (2) The damage model of SiC is defined using the JH2 model, which describes the crack initiation, damage evolution and destruction process of brittle materials.

[0009] (3) The linear elastic tensile tension law is used to define the interface layer between the SiC matrix and the carbon fiber.

[0010] (4) Establish a macroscopic drilling finite element simulation. The drilling finite element simulation analysis includes: using simulation software to construct a composite material, assigning material parameters to carbon fiber, SiC matrix and interface layer respectively, and assigning corresponding parameters to different materials according to steps (1)-(3). Divide the mesh unit type of the drill bit and the mesh unit type of the material, set the mesh size, and output simulation results, such as stress / strain, displacement / velocity / acceleration, action / reaction force, state / field, etc. Completely fix the C / SiC composite material, limit the movement and rotation of the drill bit, set the speed of the drill bit, and finally perform drilling simulation to obtain microscopic finite element simulation results.

[0011] (5) A microscopic drilling finite element simulation was established. The drilling finite element simulation analysis includes: using simulation software to construct a single carbon fiber, SiC matrix model and drill bit model, assigning material parameters to the carbon fiber, SiC matrix and drill bit models respectively, arraying the single carbon fiber model to obtain a carbon fiber bundle model, and assigning material properties to the carbon fiber bundle and SiC matrix. The carbon fiber bundle, SiC matrix and drill bit are assembled to ensure that there are different angles between the drill bit and the carbon fiber, the mesh unit type of the drill bit and the mesh unit type of the material are divided, the mesh size is set, and the simulation results are output, such as stress / strain, displacement / velocity / acceleration, action / reaction force, state / field, etc. The load is set, the bottom and side of the SiC matrix are completely fixed, the movement and rotation of the drill bit are restricted, the movement speed of the drill bit is set, and finally a microscopic finite element simulation is performed to obtain the microscopic finite element simulation results.

[0012] (6) Drilling tests were carried out. According to the drilling simulation results, the drilling process can be divided into five stages. The cross-edge drilling stage, the main cutting edge drilling stage, the main cutting edge complete drilling stage, the cross-edge drilling stage, and the main cutting edge drilling stage. In the cross-edge drilling stage, the axial force rapidly increased to 3.967N, mainly due to the squeezing effect of the cross-edge on the material. In the stable drilling force stage, the drilling force was maintained at about 4.124N, with the maximum axial force of 6.24N. Due to the anisotropy and inherent porosity of the C / SiC composite material, the instantaneous force in the stable stage varies greatly. When the drill bit acts on the pore, the force signal has a trough, and when the drill bit acts on a large area of ​​SiC matrix, the force signal has a peak. In the cross-edge drilling stage of the drill bit, the axial force rapidly decreases to 2.359N. In addition, with the increase of feed rate, the average axial force obtained from the test increases from 3.21N to 6.45N, and the axial force obtained from the simulation increases from 2.79N to 6.11N. The test value is about 10% higher than the simulation value.

[0013] (7) The finite element simulation results were compared with the drilling test. The tear factor was defined to measure the quality accuracy of the hole exit during the test and simulation. According to the results, as the feed rate increased from 0.5 μm / r to 1.5 μm / r, the hole exit tear factor obtained from the test increased from 1.17 to 1.37, and the hole exit tear factor obtained from the simulation increased from 1.18 to 1.44. The error between the simulation and test results was within 10%.

[0014] A micro-cutting model with fiber orientation angles of 0°, 45°, 90°, and 135° was established, and the material removal mechanism was analyzed. According to the simulation results, the material removal mechanism is divided into "lifting debonding type", "bending fracture type" and "shear fracture type". The surface morphology of the hole wall at different fiber orientation angles obtained in the experiment and the fracture morphology of the carbon fiber were observed and compared to verify the accuracy of the micro-cutting model.

[0015] A method for predicting the quality and material removal of micro-hole drilling in ceramic matrix composite materials, comprising:

[0016] Ceramic matrix composite materials include carbon fiber, SiC matrix, and interface layer. The damage model and performance parameters of carbon fiber, the damage model and performance parameters of SiC matrix, the damage model and material properties of interface layer are determined.

[0017] Establish a drill bit model and a ceramic matrix composite macro model in the simulation software, perform macro finite element simulation, and obtain macro finite element simulation results;

[0018] A drill bit model and a ceramic matrix composite material micromodel are established in the simulation software, and micro finite element simulation is performed to obtain micro finite element simulation results.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention provides a method for analyzing the drilling quality and material removal mechanism of micro-holes in ceramic-based composite materials, which solves the technical problem of difficulty in analyzing the drilling quality and material removal mechanism of micro-holes in ceramic-based composite materials and realizes effective quantitative characterization.

[0021] (2) The method for analyzing the quality of micro-hole drilling and material removal mechanism of ceramic-based composite materials described in the present invention can effectively replace actual experiments through simulation experiments. Considering the high cost of ceramic-based composite materials and drill bits, the cost of evaluation can be effectively reduced.

[0022] (3) The present invention establishes a C / SiC composite material model, performs drilling finite element simulation, and verifies the accuracy of the model through experiments, providing a parameter optimization basis for efficient drilling of micro-holes in ceramic-based composite materials.

[0023] (4) The present invention simulates and analyzes the drilling process of ceramic-based composite materials, which can effectively avoid the breakage and loss of the drill bit when drilling with inappropriate parameters. In addition, the analysis method is also of great significance for optimizing appropriate drilling parameters, improving the quality of hole entrances and exits, and increasing the life of the drill bit, and is suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Settings for macro drilling simulation and micro cutting simulation.

[0025] Figure 2 Figure 1. Local setup diagram for the test.

[0026] Figure 3 The drilling force signal diagram output by drilling simulation, (a) is the chisel edge drilling stage, (b) is the main cutting edge drilling stage, (c) and (d) are the main cutting edge full drilling stage, (e) is the chisel edge drilling stage, and (f) is the main cutting edge drilling stage.

[0027] Figure 4 The axial force diagram of drilling at different feed rates.

[0028] Figure 5 This is the hole exit morphology.

[0029] Figure 6 This is the schematic diagram of the tearing factor at the hole exit.

[0030] Figure 7 These are the hole outlet morphologies obtained in the experiment, f=0.5μm / r in (a), f=1.0μm / r in (b), and f=1.5μm / r in (c).

[0031] Figure 8These are the hole outlet morphologies obtained by simulation, with f = 0.5 μm / r in (a), f = 1.0 μm / r in (b), and f = 1.5 μm / r in (c).

[0032] Fig. 9 The tearing factor diagram at the hole exit corresponding to different feed rates.

[0033] Fig.10 Schematic diagram of fiber orientation angle.

[0034] Fig.11 This is the material removal process diagram when FOA=0°.

[0035] Fig.12 This is the material removal process diagram when FOA=45°. DETAILED DESCRIPTION

[0036] To make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0037] A method for analyzing the entrance and exit quality and material removal mechanism of a micro-hole (diameter Φ0.5-2mm) in a ceramic matrix composite material, comprising:

[0038] 1. Damage model and performance parameters of carbon fiber

[0039] The failure of carbon fiber mainly includes tensile failure, compression failure and shear failure, etc. In addition, carbon fiber exhibits anisotropy in mechanical properties, so the 3D-Hashin failure criterion is used to define the damage model of carbon fiber.

[0040] The values ​​of carbon fiber damage model are shown in Table 1.

[0041] Table 1 Carbon fiber damage model values

[0042] parameter Numeric Elastic modulus <![CDATA[E1=231Gpa,E2=E3=15Gpa]]> Poisson's ratio <![CDATA[ε 12 =e 13 =0.2,e 23 =0.25]]> Axial tensile strength <![CDATA[X t =4.62GPa]]> In-plane tensile strength <![CDATA[Y t =1.5GPa]]> Axial compression strength <![CDATA[X c =3.96GPa]]> In-plane compression strength <![CDATA[Y c =3.34GPa <!-- 3 -->]]> Transverse shear strength S=15GPa In-plane compression strength <h2 style=";text-align:left;direction:ltr"><![CDATA[S <h2 style=";text-align:left;direction:ltr"> I <h2 style=";text-align:left;direction:ltr"> <7GPa<h2 style=";text-align:left;direction:ltr">

[0043] 2. Damage model and performance parameters of SiC matrix

[0044] The damage model of SiC is defined by the JH2 model, which describes the crack generation, damage evolution and destruction process of brittle materials. The JH2 model parameters of silicon carbide material are shown in Table 2:

[0045] Table 2 SiC damage model values

[0046]

[0047]

[0048] 3. Damage model of interface layer and its material properties

[0049] The interface layer between the SiC matrix and the carbon fiber is defined by the linear elastic tensile tension law. The maximum secondary stress is used as the criterion for the onset of damage, and the damage model controls the stiffness of the interface layer when damage begins. The degree of damage is represented by D3, which is equal to 0 when the material is not damaged and 1 when the material is damaged.

[0050] The evolution of damage is defined based on the change in displacement, and the stiffness is assumed to soften exponentially. The parameter D3 is calculated as:

[0051]

[0052] in, is the effective separation degree at destruction, is the separation degree at the beginning of destruction, is the maximum separation degree in the whole process, and a is the destruction index.

[0054] 4. Macro finite element simulation analysis

[0055] Use modeling software to build a drill bit model, such as Figure 1 The model was imported into the simulation software, and the size parameters were 0.5 mm diameter, 130° apex angle, 10° back angle, and 30° helix angle. The handle center was set to SET-RP.

[0056] Use simulation software to build composite materials. First, select the FE module in the function interface and create a new micro unit. Create two new phases in the micro unit. The first is to establish the fiber phase, set the diameter of the carbon fiber to 7μm, the total height of a single yarn to 0.4mm, and the width to 2mm. The second is to establish the matrix phase, set the number of warp yarns to 6, the number of weft yarns to 6, and the number of braided layers to 6, and create a model. Save the model in CAE format, import it into the simulation software, and then generate the model.

[0057] Set the drill and workpiece cell types. Set the drill mesh control properties to tetrahedron, mesh division technology to free division, drill unit type to tetrahedron mesh R3D4, and mesh size to 0.0035mm. Set the mesh control properties of the woven material to hexahedron, the material unit type to hexahedron mesh C3D8R, and mesh size to 0.001mm. In "Mesh", select "Surface-New Surface" and select the drill surface. Select "Set-New Set-Node" and select the mesh on the drill path on the workpiece material.

[0058] Set the interaction type between the drill and the workpiece, set the friction coefficient to 0.3 in the tangential behavior, and set "hard contact" in the normal behavior. Click "Interaction Manager", create "Surface to Surface Contact", set "Mechanical Constraint" to Kinematic Contact Method, and set "Slip Formula" to Limited Slip.

[0059] Set cutting parameters: The speed is set to 20000r / min, and the feed rate is set to 0.5μm / r, 1.0μm / r, and 1.5μm / r respectively.

[0060] After the settings are completed, submit the job, start the macro finite element simulation, and obtain the macro finite element simulation results.

[0061] 5. Microscopic finite element simulation analysis

[0062] Draw a single carbon fiber, SiC matrix model and drill bit model in the simulation software. The diameter of a single carbon fiber is 7μm, and the SiC matrix model is 50μm long, 50μm wide and 25μm high. The drill bit has a front angle of 25°, a back angle of 7°, a height of 20μm, a width of 10μm and a thickness of 50μm. Array the single carbon fiber model to obtain a carbon fiber bundle model, and assign the carbon fiber bundle and SiC matrix material properties. Assemble the carbon fiber bundle, SiC matrix and drill bit so that the angles between the drill bit and the carbon fiber are 0°, 45°, 90° and 135° respectively, and the cutting thickness is set to 20μm.

[0063] Set the mesh size of carbon fiber and SiC to 0.001mm, and the mesh control attribute to hexahedral mesh C3D8R. Set the mesh size of drill bit to 0.01mm, and the mesh control attribute to tetrahedral mesh.

[0064] Set the friction coefficient to 0.3 in the tangential behavior and set "hard contact" in the normal behavior. Define the contact between the drill and the carbon fiber as "surface-to-surface contact", set the "mechanical constraint" to the penalty contact method, set the "slip formula" to finite slip, and assign the interaction attribute 1. Define the contact between the drill and SiC as "surface-to-surface contact", set the "mechanical constraint" to the penalty contact method, set the "slip formula" to finite slip, and assign the interaction attribute 1. Set the contact property between the carbon fiber and SiC to "general contact" and assign the interaction attribute 2.

[0065] The load was set to completely fix the bottom and side of the SiC substrate, restrict the movement and rotation of the drill bit in the X and Y directions and the rotation in the Z direction, and set the movement speed of the drill bit in the Z direction to 10 mm / min.

[0066] After the settings are completed, submit the job, start the micro finite element simulation, and obtain the micro finite element simulation results.

[0067] 6. Drilling test

[0068] The workpiece material used in this embodiment is a C / SiC composite material, and the length, width and height of the workpiece are 20 mm, 10 mm and 5 mm respectively. The diameter of a single carbon fiber is about 6-7 μm, and the volume fraction of the carbon fiber is about 30%. Other properties of the workpiece are shown in Table 4.

[0069] Table 4 Performance parameters of C / SiC composite materials

[0070] parameter Numeric <![CDATA[Density (g / cm 3 )]]> 1.72 Fiber volume (%) 30 Surface porosity (%) <10 Shear strength(MPa) 50~80 Bending strength(MPa) 400~450 In-plane compressive strength (MPa) 280 Interlaminar compressive strength (MPa) 210

[0071] The drill bit used in the test is a polycrystalline diamond (PCD) drill bit with a diameter of 0.5 mm and a main cutting edge radius of 2 μm. Other parameters of the drill bit are shown in Table 5.

[0072] Table 5 PCD drill bit structural parameters

[0073]

[0074]

[0075] This drilling experiment was carried out in the drilling center (S500X1). Figure 2 As shown. The maximum spindle speed is 20000r / min, the spindle runout is less than 1μm, and the spindle positioning accuracy is 0.1μm. During the drilling process, the drilling force is measured by a piezoelectric three-axis dynamometer and a corresponding data acquisition system. The sensitivity threshold of the piezoelectric sensor is less than 0.001N. F x 、F y and F z The natural frequency of the holes is 3.5kHz. The sampling frequency used in the experiment is 10kHz. A CCD camera is used to set the zero point and monitor the drilling process in real time. The surface morphology of the C / SiC composite material and the PCD drill bit is observed by a scanning electron microscope (SEM). The three-dimensional surface roughness of the hole wall is measured by a three-dimensional laser confocal microscope. In addition, the optical morphology of the hole entrance and exit is photographed by a microscope, such as Figure 5 shown.

[0076] 7. Comparison of simulation results with test results

[0077] (a) Drilling force

[0078] Figure 3The output drilling force cloud diagram is displayed. According to the drilling force signal, the drilling process can be divided into five stages: the cross-edge drilling stage, the main cutting edge drilling stage, the main cutting edge fully drilling stage, the cross-edge drilling stage, and the main cutting edge drilling stage. In the cross-edge drilling stage, the axial force increases rapidly to 3.967N, mainly due to the squeezing effect of the cross-edge on the material. In the stable drilling force stage, the drilling force is maintained at around 4.124N, with the maximum axial force being 6.24N. Due to the anisotropy and inherent porosity of the C / SiC composite material, the instantaneous force in the stable stage varies greatly. When the drill bit acts on the pore, the force signal has a trough; when the drill bit acts on a large area of ​​SiC matrix, the force signal has a peak. In the cross-edge drilling stage of the drill bit, the axial force decreases rapidly.

[0079] During the drilling process, the measured force signal is imported into the simulation software. First, the drift compensation function of the software is used to eliminate the signal drift. Then, the force signal is filtered using the low-pass filter function of the software with a filtering frequency of 10kHz. The reason for using low-pass filtering is that it can reduce signal fluctuations, eliminate high-frequency parts, and make the signal change smoother and slower. Next, the intercepted force signal is imported into the data calculation software. The cutting force peaks during the signal stabilization stage are counted and averaged, and the statistical data is used as the result. Figure 4 The average axial force obtained from the test and simulation at different feed rates is shown. According to the results, as the feed rate increases, the average axial force obtained from the test increases from 3.21N to 6.45N, while the axial force obtained from the simulation increases from 2.79N to 6.11N. The test value is about 10% higher than the simulation value. This is mainly because as the feed rate increases, the cutting thickness per unit time increases, resulting in an increase in the drilling force. The axial force obtained from the simulation is slightly higher than the test value because the unit deletion technology is used in the simulation process, and the influence of chips on the drilling process is not considered, so the drilling force obtained from the simulation is slightly lower.

[0080] (b) Hole outlet morphology and quality analysis

[0081] During the drilling process, the quality of the hole outlet has an important influence on the hole sealing, assembly performance, etc. Figure 6As shown in the figure, the defects that may exist at the hole exit mainly include tearing, burrs and edge collapse. The drilling stage can be divided into the chisel edge action stage and the main cutting edge action stage. In the chisel edge action stage, the extrusion effect of the chisel edge causes the carbon fiber bundle to undergo non-in-plane deformation along the drill feed direction. In the main cutting edge action stage, the main cutting edge has two functions: one is the extrusion effect on the material to debond the carbon fiber from the SiC matrix; the other is the cutting effect on the carbon fiber to cut the carbon fiber. If the carbon fiber is debonded before being cut, tearing or even delamination defects may occur. After the main cutting edge action ends, part of the carbon fiber bundle may return to the hole exit surface to form a burr defect. The cutting edge of the micro drill is longer, so the stiffness is poor. When the feed rate is large, radial runout may occur, resulting in the generation of edge collapse defects. Large-area edge collapse defects will affect the diameter and roundness of the hole, and thus affect the accuracy of the hole.

[0082] In order to more intuitively evaluate the degree of damage at the hole entrance and exit, and to study the influence of different process parameters on the damage at the hole entrance and exit, this section introduces the damage factor evaluation index. The optical morphology of the hole exit surface is photographed by a high-definition depth microscope, and the three-dimensional contour map of the hole entrance and exit surface is derived using the microscope's built-in three-dimensional contour function to measure the surface height peak and valley values. Due to the irregularity of the surface of the C / SiC composite material, it is necessary to observe the surface through a microscope before drilling to mark existing surface defects, such as inherent porosity in the material itself. Image analysis and processing software is used to identify defects such as tearing, delamination, and pits, and the depth threshold is set for identification. The damage factor is defined as (tear area A t + Target hole area A n ) / target hole area A n .

[0083] like Figure 7 , Figure 8 As shown in Figure 1, the hole exit morphology at different feed rates shows that the hole exit quality decreases with the increase of feed rate. Fig. 9 As shown in the figure, with the increase of feed rate, the tear factor of the hole outlet obtained by the test increases from 1.17 to 1.37, and the tear factor of the hole outlet obtained by simulation increases from 1.18 to 1.44. The main reason is that with the increase of feed rate, the drilling axial force increases, and the extrusion effect of the chisel edge on the carbon fiber braided layer at the hole outlet increases, resulting in an increase in the tear factor of the hole outlet. In addition, it can be observed that the tear factor of the hole outlet obtained by simulation is 4.8% higher than the experimental value. This is mainly because during the simulation process, when the material is subjected to higher stress, surface and subsurface damage will cause mesh failure. However, the damage factor obtained by the experiment can only reflect surface damage, but cannot reflect the damage of the subsurface, so the simulation results are higher than the experimental results.

[0084] (c) Material removal mechanism and micromorphology analysis

[0085] During drilling, the fiber orientation angle has a significant influence on the material removal mechanism. Fig.10 The fiber orientation angle was defined, and the material micromorphology and material removal mechanism were studied when the fiber orientation angles were 0° and 45°.

[0086] like Fig.11 As shown in the figure, when FOA = 0°, the material removal process is as follows: Initial damage occurs to the fiber at the contact point of the tool tip, and its internal stress reaches 1452Mpa. As the drill advances, the cracks expand from the inside of the fiber, causing the fiber to warp up. The top layer of fiber is subjected to the maximum stress of 823Mpa at the contact position with the front cutting edge. The lower part of the fiber is subjected to tensile stress, while the upper part is subjected to compressive stress. When the bending stress on the fiber exceeds its bending strength, the carbon fiber breaks and forms chips, and the stress is 776Mpa at this time.

[0087] When the angle between the cutting speed direction and the fiber direction is greater than 0° and less than or equal to 90°, the typical feature is that the fiber and the SiC matrix are squeezed and broken by the cutting edge. Fig.12 As shown in the figure, when FOA = 45°, the stresses at the initial damage, crack extension and chip formation stages are 691 MPa, 861 MPa and 850 MPa respectively. The initial damage is almost directly in front of the cutting edge. Due to the shear and compressive stresses, the SiC matrix is ​​completely broken into powder in the cutting edge contact area. When the shear stress on the carbon fiber exceeds its shear strength, the fiber breaks and forms chips.

[0088] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.

[0089] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.

Claims

1. A method for analyzing the drilling quality and material removal mechanism of micro-holes in ceramic matrix composite materials, characterized in that: include: Ceramic matrix composite materials include carbon fiber, SiC matrix, and interface layer. The damage model and performance parameters of carbon fiber, the damage model and performance parameters of SiC matrix, the damage model and material properties of interface layer are determined. Establish a drill bit model and a ceramic matrix composite macro model in the simulation software, perform macro finite element simulation, and obtain macro finite element simulation results; Establish a drill bit model and a ceramic matrix composite material micro-model in the simulation software, perform micro-finite element simulation, and obtain micro-finite element simulation results; Conduct drilling tests and obtain test results; The test results, macroscopic finite element simulation results and microscopic finite element simulation results are compared to verify the validity of the macroscopic finite element simulation results and microscopic finite element simulation results.

2. The method for analyzing the quality of micro-hole drilling and material removal mechanism of ceramic matrix composite materials according to claim 1, characterized in that: The 3D-Hashin failure criterion is used to define the damage model of carbon fiber.

3. The method for analyzing the quality of micro-hole drilling and material removal mechanism of ceramic-based composite materials according to claim 1, characterized in that: The JH2 model is used to define the damage model of SiC matrix.

4. The method for analyzing the quality of micro-hole drilling and material removal mechanism of ceramic matrix composite materials according to claim 1, characterized in that: The interfacial layer between the SiC matrix and the carbon fibers is defined by the linear elastic tensile tension law.

5. The method for analyzing the quality of micro-hole drilling and material removal mechanism of ceramic-based composite materials according to claim 1, characterized in that: The test results, macroscopic finite element simulation results and microscopic finite element simulation results are compared, and the comparison contents include drilling force, hole exit morphology and quality, material removal mechanism and microscopic morphology.

6. The method for analyzing the quality of micro-hole drilling and material removal mechanism of ceramic matrix composite materials according to claim 1, characterized in that: In the drilling test, the drilling force was measured by a piezoelectric three-axis dynamometer and the corresponding data acquisition system. A CCD camera was used to set the zero point and monitor the drilling process in real time. A scanning electron microscope was used to observe the surface morphology of the carbon fiber, SiC matrix and PCD drill bit. The three-dimensional surface roughness of the hole wall was measured by a three-dimensional laser confocal microscope, and the optical morphology of the hole entrance and exit was photographed using a microscope.

7. A method for predicting the quality and material removal of micro-hole drilling in ceramic matrix composite materials, characterized in that: include: Ceramic matrix composite materials include carbon fiber, SiC matrix, and interface layer. The damage model and performance parameters of carbon fiber, the damage model and performance parameters of SiC matrix, the damage model and material properties of interface layer are determined. Establish a drill bit model and a ceramic matrix composite macro model in the simulation software, perform macro finite element simulation, and obtain macro finite element simulation results; A drill bit model and a ceramic matrix composite material micromodel are established in the simulation software, and micro finite element simulation is performed to obtain micro finite element simulation results.

8. The method for predicting the quality and material removal of micro-hole drilling of ceramic matrix composite materials according to claim 7, characterized in that: The 3D-Hashin failure criterion is used to define the damage model of carbon fiber.

9. The method for predicting the quality and material removal of micro-hole drilling in ceramic matrix composite materials according to claim 7, characterized in that: The JH2 model is used to define the damage model of SiC matrix.

10. The method for predicting the quality and material removal of micro-hole drilling in ceramic matrix composite materials according to claim 7, characterized in that: The interfacial layer between the SiC matrix and the carbon fibers is defined by the linear elastic tensile tension law.

Citation Information

Cited By

  • Ceramic matrix composite processing surface defect identification and process parameter optimization method

    CN121946287A

  • Ceramic matrix composite machining surface defect identification and process parameter optimization method

    CN121946287B